BANGAN MEDIA PEMBELAJARAN KARTU UNO PADA TEMA 7 SUBTEMA 1 DI KELAS V SD - Anggi Umayrah; Eva Betty Simanjuntak (JS (JURNAL SEKOLAH), 2023)
Abstract: The purpose of this research is to determine whether the Uno Card Learning Media in Theme 7 Sub-theme 1 in Class V of Pelangi Medan Private Elementary School is feasible, practical, and effective for use in learning. This type of research is development research using the ADDIE development model. The subjects of this study consisted of material experts, learning media experts and 14 grade V students of Pelangi Private Elementary School, Medan City. The objects in this study are learning media, the scale of student responses to learning media and student learning outcomes. The results showed that the feasibility test was (1) the expert test of learning materials was in the very good classification (85.45%), (2) the learning media expert test was in the very good classification (91%), then the practicality test was in the classification very practical (91.5%). UNO Card Media Effectiveness at stage pretest student scores with an average of 55.64% in the low effectiveness category, and at stage posttest student scores increased after using the UNO Card learning media with an average of 88.5% in the "Very Good" effectiveness category. student learning outcomes increased by 32.86%, from this data it proves that the use of UNO card learning media is feasible, very practical and more effective in increasing student knowledge and competence in thematic learning. Keywords: UNO Card Media, Thematic, ADDIE Abstrak: Tujuan penelitian ini untuk apakah Media Pembelajaran Kartu Uno Pada Tema 7 Subtema 1 Di Kelas V SD Swasta Pelangi Medan layak, praktis, dan efektif digunakan dalam pembelajaran. Jenis Penelitian ini adalah penelitian pengembangan menggunakan model pengembangan ADDIE. Adapun subjek dari penelitian ini terdiri dari ahli materi, ahli media pembelajaran dan siswa kelas V SD Swasta Pelangi Kota Medan berjumlah 14 orang. Objek dalam penelitian ini adalah media pembelajaran, skala respon siswa terhadap media pembelajaran dan hasil belajar siswa. Hasil penelitian menunjukkan pada uji kelayakan adalah (1) uji ahli materi pembelajaran berada pada klasifikasi sangat baik (85,45%), (2) uji ahli media pembelajaran berada pada klasifikasi sangat baik (91%), Lalu pada uji praktikalitas berada pada klasifikasi sangat praktis (91,5%). Efektifitas Media Kartu UNO pada tahap pretest nilai peserta didik dengan rata-rata 55,64 % kategori efektifitas rendah”, dan pada tahap posttest nilai peserta didik mengalami peningkatan setelah menggunakan media belajar Kartu UNO dengan rata-rata 88,5% dengan kategori efektifitas “Sangat Baik”. hasil belajar peserta didik mengalami kenaikan sebesar 32,86%, Dari data ini membuktikan bahwa penggunaan Media belajar kartu UNO layak digunakan, sangat praktis dan lebih efektif dalam meningkatkan pengetahuan dan kompetensi siswa pada pembelajaran tematik. Kata Kunci : Media Kartu UNO, Tematik, ADDIE